Evaluation of cross-country skier performance before and after a short period of training at altitude - Poirot, X.; Guingamp, C.; Labdant, E.; Matter, F. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Most of the cross-country skiers train during short stay at altitude twice a year, during summer and autumn. However, only few studies report the effects of such training on performances (1, 2). We studied the effects of a short session of training at altitude on anaerobic and aerobic performances of cross-country skiers. Methods A group of 9 male cross country skiers (17.5±1 years old) trained during one week at Ramsau (altitude 2700 m) in Austria. They were training at low intensity twice a day during 2 h: training speed was determinated by the heart rate corresponding to the lactate threshold. Their performances were tested a few days before they leaved for Ramsau and between 5 and 8 days after they came back. Different tests specific regarding the metabolic pathway were proposed. A "Bosco ergojump" was used to measure the alactic power during the squat jump test, the counter-movement jump test and the stiffness test (containing 10 successive jumps). The lactic anaerobic capacity of the athletes was evaluated by a sub-maximal test on roller-ski on uphill road (400 m long and 8% rope) that lasted around 1 minute. Parameters of aerobic capacity were collected during a gradual running exercise on sidewalk. Speed and rope were increased successively. Many parameters were collected during and after the tests measuring the lactic anaerobic and aerobic capacities of the skiers: performances (time or power), heart rate, blood lactate at the end of the tests and after 2 min and after 5 min of rest, and the lactate thresholds during the gradual running exercise. Results The cross-country skier improved significantly their performances in squat jump (figure 1) after the training session at altitude. No change in performance was noted during the counter-movement jump test or the stiffness test. Regarding the lactic anaerobic and aerobic pathways, performances or heart rate did not change after training at altitude. However, results differed strongly according to the athlete. In contrast, significant differences in blood lactate and heart rate were observed after 2 min or after 5 min of rest: these parameters reduced more rapidly after training at altitude (figure 2 and figure 3).